Leasing: It May be Right Abroad Even When It is not at Home - Ricks, David A.; Samiee-Esfahani, Saeed (Journal of International Business Studies, 1974)
This note points out the aspects of leasing which are unique in the international environment and concludes that those unique features may make international leasing more attractive than domestic leasing.